A Vitamin B2‐Photocatalysed Approach to Methionine Analogues. (10th November 2022) - Knowles , Oliver J.; Johannissen, Linus O.; Crisenza, Giacomo E. M.; Hay, Sam; Leys, David; Procter, David J.
Abstract: Access to new non‐canonical amino acid residues is crucial for medicinal chemistry and chemical biology. Analogues of the amino acid methionine have been far less explored—despite their use in biochemistry, pharmacology and peptide bioconjugation. This is largely due to limited synthetic access. Herein, we exploit a new disconnection to access non‐natural methionines through the development of a photochemical method for the radical α‐C−H functionalization of sulfides with alkenes, in water, using inexpensive and commercially‐available riboflavin (vitamin B2 ) as a photocatalyst. Our photochemical conditions allow the two‐step synthesis of novel methionine analogues—by radical addition to unsaturated amino acid derivatives—and the chemoselective modification of peptide side‐chains to yield non‐natural methionine residues within small peptides. The mechanism of the bio‐inspired flavin photocatalysis has been probed by experimental, DFT and TDDFT studies. Abstract : Despite their emerging role in medicinal and biological chemistry, synthetic methods to access non‐natural methionine analogues remain underdeveloped. Using vitamin B2 ‐photocatalysis, simple sulfides undergo radical α‐C−H functionalization with unsaturated amino acid partners to deliver an array of new methionine derivatives. The approach also facilitates the chemoselective modification of peptide side‐chains.